2016
DOI: 10.1073/pnas.1524225113
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiologic levels of the AML1-ETO isoform AE9a are essential for transformation

Abstract: Chromosomal translocation 8;21 is found in 40% of the FAB M2 subtype of acute myeloid leukemia (AML). The resultant in-frame fusion protein AML1-ETO (AE) acts as an initiating oncogene for leukemia development. AE immortalizes human CD34 + cord blood cells in longterm culture. We assessed the transforming properties of the alternatively spliced AE isoform AE9a (or alternative splicing at exon 9), which is fully transforming in a murine retroviral model, in human cord blood cells. Full activity was realized onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…MSCV-IRES-GFP/THY.1 (MIG/MIT) and MSCV-AE-IRES-GFP/THY.1 retroviral vectors were as described. 10,20 pSIN-TREtight-DsRED-IRES and MSCV-GFP-IRES-tTA retroviral vectors were generously provided by Johannes Zuber. Insertion of AE was subcloned into pSIN-TREtight-DsRED-IRES to build an AE-tet-off system.…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCV-IRES-GFP/THY.1 (MIG/MIT) and MSCV-AE-IRES-GFP/THY.1 retroviral vectors were as described. 10,20 pSIN-TREtight-DsRED-IRES and MSCV-GFP-IRES-tTA retroviral vectors were generously provided by Johannes Zuber. Insertion of AE was subcloned into pSIN-TREtight-DsRED-IRES to build an AE-tet-off system.…”
Section: Plasmids and Reagentsmentioning
confidence: 99%
“…We and others have shown that expression of AE in human CD34 1 hematopoietic stem and progenitor cells (HSPCs) causes dysregulated differentiation and increased self-renewal of cells but without inducing AML, 9,10 serving as an ideal model to study the preleukemic stage of t(8;21) AML (AE cells). Until now, the mechanism by which AE programs progenitor cells into preleukemia with aberrant self-renewal has not been completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models of AML1-ETO-induced leukemogenesis require a truncated protein that is dramatically diminished in its ability to mediate repression (see ∆NH4 and W692A in Fig. 4), and therefore, may not be reflective of the transcriptional networks established by AML1-ETO in human disease 54 . Thus, we turned to long-term cultures of CD34 + cells from human cord blood to establish a pre-leukemic system to study AML1-ETO transcription functions.…”
Section: Rapid Loss Of Self-renewal and Differentiation Upon Degradatmentioning
confidence: 99%
“…Wang et al. found median survival in leukemic mouse models was increased via inhibition of the lysine acetyltransferase p300 (Wang et al., 2011), which reduced Lys 43 acetylation levels in AML1-ETO9a, a splice isoform of AML1-ETO (Zhang et al., 2007; Link et al., 2016). Though p300 knockdown leads to decreased acetylation, the therapeutic effects of p300 knockdown could be due to effects largely unrelated to AML1-ETO9a acetylation, indicating p300 may be a broader therapeutic target (Wang et al., 2011).…”
Section: T(8;21)mentioning
confidence: 99%